2017
DOI: 10.1186/s40854-017-0069-6
|View full text |Cite
|
Sign up to set email alerts
|

Diversification, bank performance and risk: have Tunisian banks adopted the new business model?

Abstract: Background: The objective of this paper is threefold. First, we test the most important factors that determine the level of non-interest income for Tunisian banks. Second, we study the impact of non-interest income on banks' profitability measured by both return on assets (ROA) and return on equity (ROE). Finally, we investigate the relationship between non-interest income and the level of risk taking. Methods: To achieve this goal, we used annual data of 20 Tunisian banks during the period 2005-2012. In the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 43 publications
7
38
1
1
Order By: Relevance
“…In Table 1, we can see from the results of Models (1a) that non-financing income (NFI) has a negative and significant relationship with risk (DER), which is consistent with [5,7,9,16,18]. The result shows that the increase of non-financing income will decrease the risk level so that banking service activity must be maximized.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…In Table 1, we can see from the results of Models (1a) that non-financing income (NFI) has a negative and significant relationship with risk (DER), which is consistent with [5,7,9,16,18]. The result shows that the increase of non-financing income will decrease the risk level so that banking service activity must be maximized.…”
Section: Resultssupporting
confidence: 67%
“…The study [19] shows that non-interest income as a whole is reducing bank risk in South Asia. Diversification is important because it increases bank income and also decreases the possibility of such pressure as the bank crisis [7]. Research conducted by Ekanayake and Wanamalie [4] found that risk-adjusted return on equity is positively influenced by higher non-interest income activities, indicating that a marginal increase in non-interest income increases trade-off shareholder risk.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Over the decade since the 2008 financial crisis, the literature on banking and finance has seen renewed interest in a number of areas, including the nexus between loan growth, regulation, diversification, and competition, and the development indicators for risk, capital management, and efficiency of banks (Kashif et al 2016;Bokpin 2016;Fanta 2016;Zheng et al 2017;Ozili 2017;Khraisha and Arthur 2018). Interest has also grown regarding banking industry performance in terms of allocation efficiency, risk management and profitability (Moudud-Ul-Huq 2017; Hamdi et al 2018), the application of manifold learning approaches (Huang and Kou 2014;Yan et al 2017), and the implications of Basel III for banking sector development (Ramlall and Mamode 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the following hypothesis is developed: H1: Islamic banks are different from conventional banks model A research of Karanja (2012) shows that higher non-interest income is associated with lower risk. Similarly, Hamdi et al (2017) show that diversification enhances bank income and reduces the potential of bank crises. In addition, non-interest income has a negative and significant correlation with risk.…”
Section: Risk and Service Activitiesmentioning
confidence: 98%
“…The conventional views that diversification strategies as the cost-based income sources can reduce the bank risk (Moudud-Ul-Huq, Ashraf, Gupta, & Zheng, 2018). Diversification increases bank income and reduces bank crises (Hamdi, Hakimi, & Zaghdoudi, 2017). The effect of product diversification on bank risk is related to asset size (Hidayat, Kakinaka, & Miyamoto, 2012).…”
Section: Introductionmentioning
confidence: 99%